The Application of a Scientific Approachusing the TGT Type of Cooperative Learning Model to Improve the Learning Outcomes of Throwing and Catching Balls in Ball Kasti Games - Amelya, Reski; Burhanuddin, Sudirman; Syahruddin, Syahruddin (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2021)
The study aims to improve the learning outcomes skills of throwing and catching the ball in the fourth-grade students at State Elementary School 202 Balleanging in Ujungloe subdistrict in Bulukumba district by applying the cooperative learning model of TGT type in physical education and sports to 17 fourth grade students, consisted of 10 male students and 7 female students. This study is a Classroom Action Research which was conducted in 2 cycles, that each cycle has 2 meetings and is designed through 4 stages, namely Planning, Implementation, observation, and Reflection. Then, the aspects observed in the learning process are Spiritual, Psychomotor, Affective, and Cognitive. Before conducting the research, Preliminary Observations Was conducted and the data were obtained descriptively by using the percentage of learning completeness technique based on the Minimum Completion Criteria (KKM) = 75. The results of the study reveal that the percentage of completeness of students in (Pre-cycle) is only 1 student who completes with a percentage of 5.88%, (cycle I, meeting 1) 4 students completed with a percentage of 23.52%, (cycle I, meeting 2) 6 students completed with a percentage of 35.29%, (cycle 2, meeting 1) 6 students completed with a percentage of 70.58%, (cycle 2, meeting 2) 17 students completed with a percentage of 100%. Therefore, in conclusion, the improvement of the learning outcomes skills in throwing and catching a ball in the fourth-grade students at State Elementary School 202 Balleanging in Ujungloe subdistrict in Bulukumba district by implementing the cooperative learning model of TGT type can increase significantly.